Implementasi Undang Undang Nomor 18 Tahun 2008 Tentang Pengelolaan Sampah Terhadap Masyarakat Yang Membuang Sampah Sembarangan Di Kota Bandar Lampung - Kalfin Febrian Nababan; Ardinia Awanis Shabrina; Indah Satria (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Water pollution in rivers is a serious issue that affects ecosystem life and human health. Various human activities such as industrial, agricultural, domestic waste disposal, and climate change have led to an increase in hazardous substances in river water. River water pollution can cause poisoning to aquatic organisms, kill aquatic life, and disrupt the food chain. Additionally, contaminated river water can pose various health problems for humans who consume it or use it for daily purposes. Preventing river water pollution requires serious measures, starting from strict regulations on industrial and agricultural waste, improved management of domestic waste, to public education on the importance of maintaining river cleanliness. These steps are crucial to ensure the availability of safe and clean water for all living beings and to maintain environmental balance.